Error of single-phase proton exchange membrane fuel cell model based on Brinkman-Darcy's law in different flow fields. (9th December 2019) - Chen, Shizhong; Xia, Zhongxian; Zhang, Xuyang; Wu, Yuhou
Proton exchange membrane (PEM) fuel cell is an auspicious energy device for the future with high energy efficiency and zero emissions. PEM fuel cell performance can be improved by optimising the flow field using numerical models based on Brinkman-Darcy's law. However, errors made by applying Brinkman-Darcy's law cannot be avoided; errors should be carefully investigated for different flow fields. In this paper, a single-phase PEM fuel cell model based on Brinkman-Darcy's law was developed, considering the effects of flow field on both local electrochemical active area (ECA) and effective permeability. The results showed that the model well predicted the performance of the flow field with a high resolution land width, such as 1 mm, but it over-estimated the performance under the low voltage region when the land width was 2 mm or larger, since the high mass transfer loss was under-estimated by the model.